Effect of cross-country fault of distance protection in transmission line with different voltage levels - Omar, Nur Afifah (2014)
Transmission overhead line is one of the main elements in electric power system. Electrical power system comprises of generation, transmission and distribution. For transmission lines, it is used to transmit electric power to large load center. Nowadays, double circuit transmission lines on the same tower with a different voltage are widely used. This paper present the studies of the effect on distance protection, when fault that occur in the transmission line that have different voltages in the same tower. In this situation, PSCAD/EMTDC software has been used to simulate the output current and voltages in order to see the fault effect on distance protection. In the other words, the PSCAD/EMTDC software is used in model and analysis of the effect of cross-country fault on distance protection. In this paper, the result of cross-country fault on distance protection with different voltage levels is presented.